The use of the selenised yeast additive Sel-Plex® in dairy cow diets - Phipps, Richard; Jones, Andrew; Juniper, Darren; Bertin, Gérard (MTT, 2005)
Twenty multi-parous Holstein Friesian cows were used to compare effects of an organic selenium (Se) supplement (Sel-Plex®, batch n° SEK-941, 2234 ± 198 mg Se/kg) with an inorganic Se supplement (Na2SeO3) on the performance and health of dairy cows. All cows received the same basal TMR comprising of maize silage (375 g/kg DM), grass silage (125 g/kg DM), cracked wheat (250 g/kg DM), soyabean meal (135 g/kg DM), rapeseed meal (100 g/kg DM) and mineral mixture (15 g/kg DM) providing dietary Se concentrations (mg/kg DM) of 0.15 (T1 control, no additional Se), 0.27, 0.33, 0.41 (T2-T4, Sel-Plex®) and 0.25 (T5, Na2SeO3). There were no significant treatment effects on DM intake, milk yield, milk composition, milk urea, SCC or many aspects of blood chemistry and haematology. Treatments T1 T5 had whole blood Se concentrations of 211, 214, 235, 251 and 208 µg/l, respectively. Milk Se concentrations followed a similar trend with values of 19, 28, 40, 54 and 21 µg/l for treatments T1 to T5 respectively. Corresponding Se values for urine (mg/l) and faeces (mg/kg DM) were 0.02, 0.05, 0.08, 0.14 and 0.06 and 0.37, 0.51, 0.65, 0.78 and 0.58 for treatments T1 to T5, respectively. Subsequent regression analysis indicated a significant linear (P<0.001) response of increasing dietary Se concentration on the Se content of blood, milk, urine and faeces. Pairwise comparison of treatment means for T2 (Sel-Plex®) and T5 (Na2SeO3) showed significantly (P<0.05) higher total Se concentration in milk of Sel-Plex® supplemented cows (27.8 vs. 20.8 µg Se/l), of which a greater proportion of total selenium was in the form of selenomethionine. The results of this study indicate that the use of the organic selenium additive Sel-Plex® is an effective way of increasing the Se content of milk.
Keywords: Ka; organic selenium; selenite; milk; blood; faeces; urine